Gratitude for Teenagers with Disabilities (Physical Disability) - Putri, Rukiana Novianti; Amsal, Bahrul (International Journal of Multidisciplinary Approach Research and Science, 2024)
The purpose of this study is to describe gratitude in teenagers with disabilities (physical disability). This type of research is qualitative with a phenomenological approach. The subjects are adolescents who are physically disabled. The results obtained show that gratitude is a feeling and attitude of accepting everything that has been given by God, by trying to return everything to God. Factors that influence the gratitude of adolescents with disabilities are faith in God, the presence of parents, social support (friends, parents, and living environment), religious experience. Meanwhile, the benefits obtained from the feeling of gratitude are physical health, increased ability of self-esteem, not easily despairing, living life without burden and being more patient.